Potential and toxicity effects of fish omega-3 fatty acid as a chemopreventive agent in colorectal cancer: A scoping review - Syafitri, Indah; Rahmawati, Riana; Miladiyah, Isnatin (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Colorectal cancer (CRC), a malignancy that affects the colon and rectum, is influenced by gene mutations, epigenetic changes, local inflammation, and lifestyle risk factors. New cases of CRC globally account for 10%, with mortality at 9.4%, while Indonesia occupies the top four incidence and mortality cases. A family history of CRC requires preventive measures, including consuming functional foods to maintain the colon microenvironment. This article aims to review the potency and toxicity effects of omega-3 fish fatty acids as a chemopreventive agent against CRC. The data sources were original articles about omega-3 fish fatty acids as CRC chemopreventive agents, published in 2012-2022 and in English or Indonesian. Databases used are Ovid, ScienceDirect, ProQuest, PubMed, Springer Link, EBSCO, and Google Scholar using Boolean search. The selection of studies followed the PRISMA-ScR method. Of the nine articles selected, fish omega-3 fatty acids had the potential as a chemopreventive agent against CRC, with several variations in daily dose ranges accompanied by a good lifestyle. Oral omega-3 fish supplementation gave benefits in the range of 96 mg–2,000 mg of eicosapentaenoic acid (EPA) and between 360 mg–1,000 mg of docosahexaenoic acid (DHA), with a daily intake varying between 0–14 grams/day. One study reported a toxic effect of fish omega-3 fatty acids, which raised the risk of post-operative infection after parenteral (intravenous) administration. There are no reported side effects across eight studies following oral preparation administration. The omega-3 fish fatty acid shows potential as a chemopreventive therapy for CRC; further studies are required to explore the parenteral administration-associated toxic effects.